2020
DOI: 10.3390/v12050531
|View full text |Cite
|
Sign up to set email alerts
|

Usutu Virus Infection of Embryonated Chicken Eggs and a Chicken Embryo-Derived Primary Cell Line

Abstract: Usutu virus (USUV) is a mosquito-borne flavivirus, closely related to the West Nile virus (WNV). Similar to WNV, USUV may cause infections in humans, with occasional, but sometimes severe, neurological complications. Further, USUV can be highly pathogenic in wild and captive birds and its circulation in Europe has given rise to substantial avian death. Adequate study models of this virus are still lacking but are critically needed to understand its pathogenesis and virulence spectrum. The chicken embryo is a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…No strains from Europe 4 and Europe 5 lineages have been tested yet for their pathogenicity either in vitro or in vivo. Further, only one study [ 71 ] compared the replication kinetics, indicative of the virulence of four USUV strains (Africa 3 and Europe 1, 2, and 3 lineages), in chicken embryo primary cells and found marked replication of the Europe 3 strain compared to the others. However, in vivo studies using chicken embryos revealed similar pathogenicity between these strains, indicating the importance of combining different models from which to draw robust conclusions.…”
Section: In Vitro Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…No strains from Europe 4 and Europe 5 lineages have been tested yet for their pathogenicity either in vitro or in vivo. Further, only one study [ 71 ] compared the replication kinetics, indicative of the virulence of four USUV strains (Africa 3 and Europe 1, 2, and 3 lineages), in chicken embryo primary cells and found marked replication of the Europe 3 strain compared to the others. However, in vivo studies using chicken embryos revealed similar pathogenicity between these strains, indicating the importance of combining different models from which to draw robust conclusions.…”
Section: In Vitro Modelsmentioning
confidence: 99%
“…Similar to WNV, death due to USUV in domestic canaries was more likely attributed to a multi-systemic failure than to a pure neurologic disease, and the virus infected all major systems and a wide variety of cell types [ 110 ]. The myocardial cells strongly supported viral replication, as viral antigens were systematically detected by immunohistochemistry (IHC) in the experimentally infected chicken embryos and canaries [ 71 , 110 ].…”
Section: In Vivo Modelsmentioning
confidence: 99%
See 3 more Smart Citations